A business plan and strategy for TASTE ST LOUIS catering and vending - Prindiville, Paula (Kansas State University, 2010)
This thesis is the plan used to outline a business plan for a prospective business, TASTE ST LOUIS. While working toward my MAB Degree, I realized there were many things I could implement from the program into the business that would help this new business venture to succeed. I was able to research the food service industry to gain a better understanding of how to market and plan for the success of this venture. After I started the research on this business venture, I soon found that we needed a business plan that would answer many questions we had regarding the success of our business. The first part of the thesis is a brief summary of the food service businesses in St. Louis and the geographic analysis that became the deciding factor in locations. The second part of the thesis is an explanation of TASTE ST LOUIS. This section gives the history of the business and explains the development and start-up. The third portion, of the thesis is the small- business plan and pro forma financial statements.
Keywords: Food service; Mobile food service; Small business; Business planning; Vending business; Marketing food service; Economics, Agricultural (0503)